2018
DOI: 10.1016/j.vaccine.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

An innovative medical school curriculum to address human papillomavirus vaccine hesitancy

Abstract: Our innovative curriculum improved medical student comfort level discussing HPV vaccination with hesitant parents and increased the perceived likelihood of recommending HPV vaccination. The intervention is easy to implement, scalable, and requires minimal resources. Educating future providers on this important topic has the potential to improve vaccination rates nationwide and thus should be considered for all medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 23 publications
(32 reference statements)
0
28
0
Order By: Relevance
“…case-based curricular methods coupled with interactive small group discussions, simulation training, communication strategies to address vaccine hesitancy) to improve knowledge and promote HPV vaccine recommendations. 44 Given the high burden of cervical cancer and other HPV-associated diseases in India, medical and paramedical students can play a pivotal role in implementing a successful HPV immunization program as future health care providers. Future studies should also evaluate implementation of population-based cervical cancer screening and perform comparative cost-effectiveness analysis of HPV vaccination strategy versus cervical cancer screening in India.…”
Section: Discussionmentioning
confidence: 99%
“…case-based curricular methods coupled with interactive small group discussions, simulation training, communication strategies to address vaccine hesitancy) to improve knowledge and promote HPV vaccine recommendations. 44 Given the high burden of cervical cancer and other HPV-associated diseases in India, medical and paramedical students can play a pivotal role in implementing a successful HPV immunization program as future health care providers. Future studies should also evaluate implementation of population-based cervical cancer screening and perform comparative cost-effectiveness analysis of HPV vaccination strategy versus cervical cancer screening in India.…”
Section: Discussionmentioning
confidence: 99%
“…Further emphasizing the need for future HCPs to be well equipped to confidently and knowledgeably address immunization in their future careers. Research conducted both in the U.S. and internationally have shown that education focused on providing future HCPs with strategies to address vaccine hesitancy, along with education with multidisciplinary teams, can significantly improve students’ knowledge and confidence related to immunizations [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…human papillomavirus [HPV] vaccine, influenza vaccine) [8, 13, 14, 25, 26]. Comparisons have not been sought between HCP programs [8, 13, 14, 25, 26]. Greater understanding of the training HCPs receive could provide insight into how their vaccine knowledge, attitudes, and beliefs are formed and how to better equip HCP students to address immunizations in their future careers.…”
Section: Introductionmentioning
confidence: 99%
“…The current trend suggests a relatively low level of awareness on HPV-associated diseases in males and acceptability of vaccination against the virus in most countries but worst in developing nations [75][76][77][78][79]. There are efforts from varying perspectives by different groups to improve the current situation based on findings from some studies [80,81].…”
Section: Future Perspectives On Hpv In Malesmentioning
confidence: 99%